Some aspects of preparation of future teachers of physical training for creative teaching activity - Bondar T.S; Novik O.O; Ostrikova J.O (Kharkov National Pedagogical University, 2012)
It is considered the influence of special training cycle directed on the forming and development of creative abilities in future teachers of physical culture. In pedagogical experiment participated 99 students of the full-time faculty "Physical education" (experimental group - 45 persons). Proved growth rates of fluency, flexibility of thinking and elaboration of ideas in the experimental group. It is established that proposed cycle training did not significantly impact on the improvement manifestations of originality of thought.